Positive Behavioral Interventions and Supports in Secure Care Juvenile Justice Settings: Feasibility and Sustainability. (August 2019) - Scheuermann, Brenda; Parsons, Madeline; Hayes, Karena
The success of positive behavioral interventions and supports (PBIS) in typical schools has led to interest in applying PBIS in alternative settings, including secure care programs for incarcerated juveniles. PBIS holds promise for positively impacting youth behavior in this context. In this discussion article, we describe unique characteristics of secure care and strategies to enhance PBIS implementation and sustainability.